Accuracy of the Short-Form Montreal Cognitive Assessment Chinese Versions - Tan, Ji-ping; Wang, Xiaoxiao; Zhang, Shimin; Zhao, Yiming; Lan, Xiaoyang; Li, Nan; Wang, Lu-ning; Gao, Jing (Frontiers in Aging Neuroscience, 2021)
Background There is a strong need for short and effective methods to screen for cognitive impairment. Recent work has created short forms of the Montreal Cognitive Assessment (s-MoCA) in English speaking populations. It is also important to develop a validated Chinese short version to detect cognitive impairment. Methods Item response theory and computerized adaptive testing analytics were used to construct abbreviated MoCAs across a large neurological sample comprising 6,981 community-dwelling Chinese veterans. Results Six MoCA items with high discrimination and appropriate difficulty were included in the s-MoCA. The Chinese short versions (sensitivity 0.89/0.90, specificity 0.72/0.77) are similar in performance to the full MoCA in identifying cognitive impairment (sensitivity 0.91, specificity 0.82). Conclusions These short variants of the MoCA may serve as quick and effective instruments when the original MoCA cannot be feasibly administered in clinical services with high patient burden and limited cognitive testing resources.